EKSPLORASI KEMAMPUAN REFLEKTIF SISWA DALAM MEMECAHKAN MASALAH KONTEKSTUAL BERBASIS DEEP LEARNING PADA PEMBELAJARAN AKIDAH AKHLAK DI MADRASAH TSANAWIYAH NEGRI 1 KOTA JAMBI - Putri Helsa; Arif Wiratama (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study explores students’ reflective abilities in solving contextual problems through deep learning-based Akidah Akhlak instruction at MTs Negeri 1 Kota Jambi. The research was motivated by the limited ability of students to relate Islamic values to real-life situations and the dominance of teacher-centered learning in the classroom. The purpose of this study was to analyze students’ reflective abilities, the implementation of deep learning-based instruction, and the role of the Merdeka Curriculum in supporting reflective learning. This research employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation involving students of class VIII F and the Akidah Akhlak teacher. Data analysis techniques included data reduction, data display, and conclusion drawing. The findings revealed that students’ reflective abilities gradually developed through contextual and interactive learning activities such as discussion, problem-solving, and reflection sessions at the end of learning. Students were able to understand the meaning of the learning material, connect it with daily life experiences, and evaluate their attitudes based on Akidah Akhlak values. Furthermore, the implementation of the Merdeka Curriculum contributed to creating active, flexible, and student-centered learning environments that supported the development of reflective thinking. This study implies that teachers need to continuously develop deep learning-based instruction to strengthen students’ reflective abilities and encourage meaningful Islamic learning experiences